Investigation on Free Vibration of Rotating Cylindrical Shells with Variable Thickness - Liu Xiangdong; Hou Xiaoli; Bai Bin; Zeng Maolin (Shock and Vibration)
In order to improve the performance and efficiency of the rotating cylindrical shell (RCS), one of the effective ways reduces the mass of the RCS. The scientific and effective method is to design the variable thickness of RCS (VTRCS) along the axial direction in response to this demand. Then, the vibration traveling wave characteristics of VTRCS are investigated by Chebyshev–Ritz method. The displacement field of the cylindrical shell is expanded in the form of the product of the Chebyshev polynomial and the boundary function. The kinetic and potential energies of the VTRCS are calculated based on the Sanders shell theory considering the effects of Coriolis forces and centrifugal forces. Also, the frequency equation of the VTRCS is obtained according to the Ritz method. The accuracy of the modeling method is verified by comparing the present results with literature that had done, and the convergence of the calculated results is studied. Finally, the free-vibration traveling wave characteristics of the VTRCS in different thickness variations are compared, and the parameters such as the rotational speed, thickness variation parameters, and aspect ratio on the free-vibration traveling wave characteristics of the VTRCS are discussed. The influence of thickness variation on the vibration characteristics is analyzed, which has significance for the lightweight design for VTRCS.